Theological Biblical Reflection on Women and Mission Based on the Hermeneutic Study of Mark 16:180 - Mieke Nova Sendow; Deny Adri Tarumingi (International Journal of Integrated Science and Technology, 2024)
The Resurrection of Jesus is a part of history which has a great impact for the Christian’s life. The Resurrection is not only a story, but a real history which encourage the Christian to keep on believing in God and the Living Jesus Christ. This research with historical criticism aims to reveal how The Resurrection was primarily witnessed by the women. The women whom did not have a place and voiceless in the community carry the mission to deliver the good news of resurrection. The result of biblical theology reflection shown that God’s Mission been carried by the women being the reflectional base for the church now to not be afraid and hesitate to tell the Good News about The Risen Jesus Christ.